The effects of sodium tanshinone IIa sulfonate pretreatment on high glucose-induced expression of fractalkine and apoptosis in human umbilical vein endothelial cells - Li, Fa-Qi (Int J Clin Exp Med, 2015)
The development of diabetes mellitus (DM) and its complications is a chronic inflammatory response process, chemokines and their receptors play an important role in this course of events. The aim of this study is to observe the effects of sodium tanshinone IIa sulfonate (STS) on high glucose-induced fractalkine (FKN) level, and investigate possible mechanisms of STS works. HUVECs cells were employed to explore the effects of STS on FKN protein. TUNEL assay was used to detect the apoptosis rate of HUVECs. Immunohistochemistry was utilized to detect the β-actin and P-GSK-3β (Ser9) protein expression. Immunofluorescence was employed to detect FKN protein expression. Real-time RT-PCR was used to examine β-actin, GSK3β and FKN mRNA expression. The results indicated that the STS treatment could significantly decrease the apoptosis rate caused by high-glucose (P < 0.05). STS improves β-catenin and p-GSK-3β (Ser9) expression, and inhibits FKN levels induced by high glucose. STS inhibited GSK-3β and FKN mRNA induced by high glucose. In conclusion, STS may play the role of anti- inflammatory by regulate canonical Wnt pathway to inhibit the expression of FKN induced by high glucose.